Computer algorithms for three-dimensional measurement of humeral anatomy: analysis of 140 paired humeri - Vlachopoulos, Lazaros; Dünner, Celestine; Gass, Tobias; Graf, Matthias; Goksel, Orcun; Gerber, Christian; Székely, Gábor; Fürnstahl, Philipp (Journal of shoulder and elbow surgery, 2016)
In the presence of severe osteoarthritis, osteonecrosis, or proximal humeral fracture, the contralateral humerus may serve as a template for the 3-dimensional (3D) preoperative planning of reconstructive surgery. The purpose of this study was to develop algorithms for performing 3D measurements of the humeral anatomy and further to assess side-to-side (bilateral) differences in humeral head retrotorsion, humeral head inclination, humeral length, and humeral head radius and height. The 3D models of 140 paired humeri (70 cadavers) were extracted from computed tomographic data. Geometric characteristics quantifying the humeral anatomy in 3D were determined in a semiautomatic fashion using the developed computer algorithms. The results between the sides were compared for evaluating bilateral differences. The mean bilateral difference of the humeral retrotorsion angle was 6.7° (standard deviation [SD], 5.7°; range, −15.1° to 24.0°; P = .063); the mean side difference of the humeral head inclination angle was 2.3° (SD, 1.8°; range, −5.1° to 8.4°; P = .12). The side difference in humeral length (mean, 2.9 mm; SD, 2.5 mm; range, −8.7 mm to 10.1 mm; P = .04) was significant. The mean side difference in the head sphere radius was 0.5 mm (SD, 0.6 mm; range, −3.2 mm to 2.2 mm; P = .76), and the mean side difference in humeral head height was 0.8 mm (SD, 0.6 mm; range, −2.4 mm to 2.4 mm; P = .44). The contralateral anatomy may serve as a reliable reconstruction template for humeral length, humeral head radius, and humeral head height if it is analyzed with 3D algorithms. In contrast, determining humeral head retrotorsion and humeral head inclination from the contralateral anatomy may be more prone to error.